2010
DOI: 10.1021/np100337j
|View full text |Cite
|
Sign up to set email alerts
|

Dolabellane Diterpenoids from the South Atlantic Gorgonian Convexella magelhaenica

Abstract: Two new dolabellane diterpenoids (1 and 2) were isolated from a small sample of the deep water gorgonian octocoral Convexella magelhaenica collected as a nontarget by-catch by dredging (-93 m) in commercial Patagonian scallop fishing grounds in the South Atlantic. The structures of the new compounds, which are major metabolites in the extract, were established by spectroscopic techniques and chemical transformations. Both compounds were cytotoxic against a human pancreatic adenocarcinoma cell line at micromola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Scallop sled bycatch from a deep water South Atlantic site included specimens of the sea whip Convexella magelhaenica, investigation of which yielded mildly cytotoxic dolabellanes 760 and 761. 706 Cembranoids sarcocrassocolide A-E 762-766 (Sarcophyton crassocaule, Dongsha Atoll, Taiwan) were mildly cytotoxic and also inhibited the expression of iNOS in macrophages. 707 The known co-metabolite sarcocrassolide 708 was a potent inhibitor of the expression of COX-2 protein in the same cell line.…”
Section: Cnidariansmentioning
confidence: 99%
“…Scallop sled bycatch from a deep water South Atlantic site included specimens of the sea whip Convexella magelhaenica, investigation of which yielded mildly cytotoxic dolabellanes 760 and 761. 706 Cembranoids sarcocrassocolide A-E 762-766 (Sarcophyton crassocaule, Dongsha Atoll, Taiwan) were mildly cytotoxic and also inhibited the expression of iNOS in macrophages. 707 The known co-metabolite sarcocrassolide 708 was a potent inhibitor of the expression of COX-2 protein in the same cell line.…”
Section: Cnidariansmentioning
confidence: 99%
“…Preliminary results demonstrated that sponges are also responsible for the majority of the organic and inorganic carbon fixation (Bergagna, ). Additionally, cnidarians and sponges have been shown to harbour natural marine products of interest for biotechnology development (Molinski, Dalisay, Lievens, & Saludes, ; Patiño Cano et al, , ; Rojo de Almeida et al, ), and constitute some of the in‐progress studies of the area with promising preliminary results (Prieto et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…83,84 Anthozoans are the most abundant class of cnidarians with over 6500 species known. 86 The cnidarian Echinogorgia pseudossapo (from Sanya, Hainan Province, P.R. The deep-sea cnidarian Acanthoprimnoa cristata collected by dredging at a 138 m depth in the Yakushima-Shinsone, Kagoshima Prefecture, Japan, yielded a new xenicane diterpenoid, cristaxenicin A (5) that exhibited potent antiprotozoal activities against Leishmania amazonensis and Trypanosoma congolense with IC 50 values of 88 and 250 nM, respectively.…”
Section: Cnidariamentioning
confidence: 99%
“…85 Two new dolabellane diterpenoids (6 and 7) were also reported from the cnidarian Convexella magelhaenica collected from the South Atlantic by dredging at a depth of 93 m. Both 5 and 6 exhibited signicant cytotoxic activities against a human pancreatic adenocarcinoma cell line at micromolar concentrations. 86 The cnidarian Echinogorgia pseudossapo (from Sanya, Hainan Province, P.R. China) was the source of two new alkaloids, pseudozoanthoxanthins III and IV (8 and 9) and two new sesquiterpenes (10 and 11).…”
Section: Cnidariamentioning
confidence: 99%